THE CATEGORY OF EXPRESSIVENESS AND IMAGERY OF SPEECH - Popova Elena Ivanovna (Web of Journals Publishing, 2025)
The article correlates the concepts of expressiveness, imagery, and pictorial speech. The ability of a word to create visual and sensory images (pictures) of objects and phenomena of the surrounding world in philology is determined. Three types of imagery are described: potential, evident, and artistic. The nature and sources of expressiveness at different levels of language are considered. The ability of speech expressiveness to be contextual and textual is indicated. The ways of distinguishing the categories of expressiveness and depiction are determined.
Keywords: word, concept, image, potential imagery, evident imagery, artistic imagery, poetic language, expressiveness of speech, expressive means of language